Specific Aspects of Forecasting and Perception of the Norm by Juniour Schoolchildren with Developmental Disorders - Anna I. Akhmetzyanova; Tatyana V. Artemyeva; Alla A. Tvardovskaya (National Research Mordova State University, 2017)
Introduction: juniour schoolchildren with special needs should take into account the existing system of norms and rules in the school space. They should understand both their own inner world and that of surrounding people, but in conditions of deficiency dysontogenesis, the inability to forecast the outcome of any situation and the use of irrational behavioural strategies reduce the opportunities for successful social adaptation. The purpose of this study is to identify the specifics of forecasting and understanding normative situations by juniour schoolchildren with musculoskeletal system disorder, as well as with vision, hearing and speech impairment. Materials and Methods: to study the forecasting specifics of juniour schoolchildren, we used the guessing game methodology by L. I. Peresleni. We studied the specific character of normative behaviour using a set of methodologies: Perception of the normative situation by A. K. Pashchenko, Anticipation of the outcome with violation of the norm by V. P. Ulyanova, and Identification of the cultural congruity of juniour schoolchildren by L. F. Bayanova. Results: the study made it possible to identify the forecasting characteristics of juniour schoolchildren with normative development and with vision, hearing, speech impairments and musculoskeletal disorder. Students with developmental disabilities experienced forecasting difficulties, associated with decreasing sustainability of voluntary attention and its distribution in the course of the activity. The perception of norms by schoolchildren with developmental disorders often depended on random, brightly coloured emotional events or objects. The norms were differentiated more successfully in a situation of communication, than in educational activity. Discussion and Conclusions: the obtained data are consistent with the results of the studies by national and foreign scientists, who note that children with health limitations lack understanding of the need to comply with social norms. They follow irrational strategies for forecasting and assessing their own actions and the behaviour of people around them. However, these studies are fragmentary; not all types of deficiency development have been studied. The aspects of forecasting normative behaviour of schoolchildren with health limitations in the situations of social interaction revealed in the study can be useful in the development of diagnostic tools that make it possible to evaluate the prognostic ability of a child with developmental disorders and to assess the risks of socialisation disorders.